2012
DOI: 10.1021/pr2009252
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Profiles Discriminate Hepatocellular Carcinoma from Liver Cirrhosis by Ultraperformance Liquid Chromatography–Mass Spectrometry

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and usually develops in patients with liver cirrhosis (LC). Biomarkers that discriminate HCC from LC are important but are limited. In the present study, an ultraperformance liquid chromatography-mass spectrometry (UPLC-MS)-based metabonomics approach was used to characterize serum profiles from HCC (n = 82), LC (n = 48), and healthy subjects (n = 90), and the accuracy of UPLC-MS profiles and alpha-fetoprotein (AFP) levels were compared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 46 publications
7
107
0
Order By: Relevance
“…29,30 A UPLC-MS-based metabolomics approach has been used to characterize serum profiles from HCC, liver cirrhosis (LC), and healthy subjects, and the accuracy of UPLC-MS profiles and AFP levels were compared for their use in HCC diagnosis. 31 Thirteen potential biomarkers were identified that suggest there were significant disturbances of key metabolic pathways in HCC patients. Of note, glycochenodeoxycholic acid was suggested to be an important indicator for HCC diagnosis and disease prognosis.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 99%
“…29,30 A UPLC-MS-based metabolomics approach has been used to characterize serum profiles from HCC, liver cirrhosis (LC), and healthy subjects, and the accuracy of UPLC-MS profiles and AFP levels were compared for their use in HCC diagnosis. 31 Thirteen potential biomarkers were identified that suggest there were significant disturbances of key metabolic pathways in HCC patients. Of note, glycochenodeoxycholic acid was suggested to be an important indicator for HCC diagnosis and disease prognosis.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 99%
“…Canavaninosuccinate was first identified as a metabolite that is significantly reduced in liver cirrhosis and increased in HCC. In addition, GCDCA was suggested to be an important indicator for HCC diagnosis and disease prognosis [32]. Chronic liver diseases including chronic hepatitis B and hepatic cirrhosis are the major risk factors for development of HCC.…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 99%
“…Novel metabolic markers are therefore a promising supplement to classic biomarkers. The combination of metabolic markers and traditional protein-based markers will be a trend in future biomarker applications [101][102][103].…”
Section: Translational Research On Tumor Metabolic Markersmentioning
confidence: 99%